Glucose sensing module - is it time to integrate it into real-time perioperative monitoring? An observational pilot study with subcutaneous sensors - Poljaková, Iveta; Elšíková, Eva; Chlup, Rudolf; Kalabus, Stanislav; Hasala, Petr; Zapletalová, Jana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2013)
AIMS: To explore the feasibility of subcutaneous continuous glucose monitoring (CGM) in perioperative settings and to evaluate the perioperative development of glycaemia in persons with diabetes mellitus or impaired glucose tolerance by means of CGM. METHODS: Monitoring by means of Guardian REAL-Time CGMS (Medtronic, Nortridge, USA) in 20 perioperative periods. Sensor was inserted on the day before surgery and continued for 3 days with some exceptions. RESULTS: Full implementation of the method was successful in the intensive care unit setting only. No electromagnetic interference and no side effects were found. The Wilcoxon signed-rank test revealed no significant difference between sensor and laboratory analyser values. Pearson's correlation coefficients of the values obtained by sensor and the Wellion Linus glucometer were 0.875 for the whole perioperative period, 0.866 for the intraoperative period and 0.903 for the first perioperative day. A decline in sensor accuracy on the 6(th) day was registered in one case. 16 monitored cases (80%) did not meet the criteria for safe plasma glucose range. Hypoglycaemia was found in 4 (20%) cases. There was an association between grade of the perioperative dysglycaemia and need for reoperation within the next 3 months. The most frequent perioperative glycaemic patterns are demonstrated. CONCLUSION: Subcutaneous CGM is safe offering detailed insight into glucose homeostasis in the dynamic perioperative period. Laboratory confirmation of sensor plasma glucose concentration by approved laboratory analyser is still necessary. The potentional benefits of maintaining patients within a safe glucose range should be comfirmed by future studies.
Keywords: Aged; Perioperative Care; senioři; počítačové systémy; Blood Chemical Analysis; Subcutaneous Tissue; lidé; pilotní projekty; Prostheses and Implants; Blood Glucose; krevní glukóza; subkutánní tkáň; Female; perioperační péče; Male; ženské pohlaví; Humans; studie proveditelnosti; mužské pohlaví; Feasibility Studies; Computer Systems; Pilot Projects; protézy a implantáty; biochemická analýza krve